2012
DOI: 10.1118/1.4767756
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Doppler broadening and detector resolution on the performance of three‐stage Compton cameras

Abstract: Purpose:The authors investigated how the characteristics of the detectors used in a three-stage Compton camera (CC) affect the CC's ability to accurately measure the emission distribution and energy spectrum of prompt gammas (PG) emitted by nuclear de-excitations during proton therapy. The detector characteristics they studied included the material (high-purity germanium [HPGe] and cadmium zinc telluride [CZT]), Doppler broadening (DB), and resolution (lateral, depth, and energy). Methods:The authors simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…Several studies focused on optimizing the geometry and materials of three‐stage CCs . Moreover, Mackin et al evaluated the effects of Doppler broadening and detector resolution on the performance of three‐stage CCs. Polf et al showed the feasibility of using a prototype CC to image PG rays emitted during proton beam irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies focused on optimizing the geometry and materials of three‐stage CCs . Moreover, Mackin et al evaluated the effects of Doppler broadening and detector resolution on the performance of three‐stage CCs. Polf et al showed the feasibility of using a prototype CC to image PG rays emitted during proton beam irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The DCA is defined as the shortest distance between the source position and the cone-of-origin surface [15, 24]. In previous applications [15, 24], DCA has been used as a metric to understand how the physical characteristics of a CC affect characteristics of a detected γ cone-of-origin, and how these effects impact image reconstruction.…”
Section: D2c Imaging Methodsmentioning
confidence: 99%
“…In previous applications [15, 24], DCA has been used as a metric to understand how the physical characteristics of a CC affect characteristics of a detected γ cone-of-origin, and how these effects impact image reconstruction. In this work DCA is used to process the measured data in two different ways.…”
Section: D2c Imaging Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental approaches considered so far are based on tracking secondary protons, [2][3][4][5] detecting prompt-c emission, 6,7 or performing online PET gamma reconstruction. [8][9][10] Several modalities for prompt-c imaging have been investigated: collimated cameras, [11][12][13][14][15] compton cameras [16][17][18][19][20][21][22][23] and prompt-c timing. 24 One important parameter is the production yield of secondary particles used in these methods during treatment, as this will affect the accuracy of the reconstructed dose distribution.…”
Section: Introductionmentioning
confidence: 99%